2022
DOI: 10.1108/jhtt-03-2021-0093
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effect of marketing activities toward augmented reality: the perspective of extended customer experience

Abstract: Purpose In this era of smartphone applications, brands are actively developing applications to occupy the consumer’s mobile phone space, adding many practical functions to their applications to increase brand exposure or consumer interest in the brand. Augmented reality (AR) has evolved rapidly in the past decade because of technological breakthroughs, making AR no longer an untouchable technology, but one that can be easily used on almost every phone. Therefore, this study aims to combine extended customer ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
0
14
0
1
Order By: Relevance
“…This satisfaction results in engagement with the online website. Engagement results in a pleasurable shopping experience, which is likely to lead to increased usage and adoption of the AR 14,21 . The greater product knowledge increases risk perception when buying online.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This satisfaction results in engagement with the online website. Engagement results in a pleasurable shopping experience, which is likely to lead to increased usage and adoption of the AR 14,21 . The greater product knowledge increases risk perception when buying online.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown how AR favours the engagement generated with the online shop [11][12][13][14] . These studies have focused on explaining how these consequences are generated through aspects such as interactivity, vividness, utilitarian and hedonic benefits, usefulness or customisation.…”
Section: Introductionmentioning
confidence: 99%
“…Authors Example of research question TAM 15 Butt et al, 2022;Chen et al, 2022;Cuomo et al, 2020;de Silva et al, 2019;Do et al, 2020;Erra et al, 2018;Jiang et al, 2019;Lee et al, 2017;McLean & Wilson, 2019;Park & Stangl, 2020;Phuthong, 2022;Perannagari & Chakrabarti, 2019;Plotkina & Saurel, 2019;Watson et al, 2020 "Investigate whether AR-based VTO tools are more effective than pictures of human models in the m-commerce setting." (Plotkina & Saurel, 2019, p. 363) Experience economy (four realms) 10…”
Section: Number Of Articlesmentioning
confidence: 99%
“…The third theme is based on extended reality (XR), which covers VR, AR, and mixed reality (MR). XR technology moves the human interaction into a virtual and/or hybrid mode, and the applications in hospitality situations include labour training, tourism destination simulation and commercial marketing (Chang and Chiang, 2022; Chen et al , 2022; Leung et al , 2022; Lui and Goel, 2022; Santoso et al , 2022). The fourth theme is marketing technology (MarTech) which is important in the hospitality industry and will help the firms to use social media, online reviews and other similar range of software and tools to achieve marketing goals (Zhuo and Wang, 2022).…”
Section: Smart Hospitality Themes In Hospitality and Tourism Marketingmentioning
confidence: 99%